EVALUATION OF THE SPECIFIC PHYSICAL DEVELOPMENT OF THE CYCLISTS AT THE AGE OF 13 TO 14 YEARS - Iv. Kolev (Trakia Journal of Sciences)
Ascending level of sport performance in cycling and immense competition in the struggle of world hegemony in this sport require continuous quality improvement and efficiency of educational and training processes. For the purpose of the study was conducted assessing of the level of indexes presenting physical development and specific performance of all respondents (13-14-year-old). Results and discussion. The use of evaluation (through sigmal method) allows comparing the level of all monitored indexes, regardless of the different measuring units, and on this basis to determine the highlights for future training process for each respondent individually. For solving the purpose and objectives of the following study, individual results of each respondent are assessed based on average level results of each index included in the test battery for selection and evaluation of physical development and specific sport performance. Conclusions. The group of 13-14-year-olds as a whole, is well selected, but the possibilities of 6 children included in it currently does not meet the specific requirements of sport cycling. We need to be much effort in working with these children, the highlights are aimed at developing the signs, which estimates T are lowest.